Brown Rice: Nutritional composition and Health Benefits - Upadhyay, Atul; Karn, Sanjeev Kumar (Journal of Food Science and Technology Nepal, 2018)
Brown rice is the unmilled rice with pericarp, the seed coat and nucellus, the germ or the embryo, and the endosperm. It is whole grain rice with intact bran layer and the inedible outer hull removed. Although it has several health claims, it is mostly consumed by a limited number of health conscious and nutritionally aware people. In this paper, we discuss the physiochemical properties of brown rice along with its health benefits, including certain cancers.